Characterization of the C-type lectin from the marine sponge (Stylissa flexibilis) - Hung, Le Dinh; Thanh Trung, Dinh (Vietnam Journal of Biotechnology, 2020)
A lectin from the marine sponge Stylissa flexibilis, designated as SFL, was purified by cold ethanol precipitation followed by ion exchange chromatography on DEAE Sepharose column and Sephacryl S-200 gel filtration. SFL is a dimeric glycoprotein of 32 kDa subunits linked by a disulfide bridge with a molecular mass of 64 kDa by SDS-PAGE and 65 kDa by Sephacryl S-200 gel filtration chromatography. The lectin preferentially agglutinated enzyme treated human A erythrocytes, whereas it did not agglutinate any type of rabbit, human B and O erythrocytes, irrespective of treatment with enzymes. The hemagglutination activity of lectin was strongly inhibited by monosaccharide, D-galactose and glycoproteins, asialo-porcine stomach mucin and asialo-fetuin, indicating that lectin is specific for O-glycans. Activity of SFL was stable over a range of pH from 5 to 8, up to 60 °C for 30 min and its activity was Ca2+ dependent, indicating that SFL was belonged to the C-type lectin family and requires metal for biological activity. SFL caused agglutination of Vibrio alginolyticus and V. parahaemolyticus in a dose dependent manner and inhibited the growth rate of these bacterial strains, suggesting that the lectin caused the agglutination through binding to the target receptor(s) on the surface of Vibrios. Thus, SFL can be considered as a good source of lectin(s) being useful as carbohydrate probe and antibacterial reagent.